On the uses of Hume’s history - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2018)
Much of the conversation now coming to an end has centered on Hume's History of England and on his use of history to serve his political philosophical purposes. Dan Klein has appealed to the History by citing more and more chapters and verses to illustrate and reinforce his thesis that "mere liberty" was central to Hume's concerns. Nicholas Capaldi concurs (having originally advanced the claim that liberty was the default value for the pluralist Hume), suggesting that getting the historical narrative right was important for Hume, as it must be for all defenders of (mere) liberty. Capaldi's response to the challenges put by those of us who dissent from his view has been to state that view anew, each time in slightly different form. I remain unconvinced by either of these scholars because I do not see that they have addressed the objections leveled against their views rather than simply supplied more of the same.